Progress on the Regulation of Ruminant Milk Fat by Noncoding RNAs and ceRNAs - Lu, QinYue; Chen, Zhi; Ji, Dejun; Mao, Yongjiang; Jiang, Qianming; Yang, Zhangping; Loor, Juan J. (Frontiers in Genetics, 2021)
Milk fat is not only a key factor affecting the quality of fresh milk but also a major target trait forbreeding. The regulation of milk fat involves multiple genes, network regulation and signal transduction. To explore recent discoveries of pathway regulation, we reviewed the published literature with a focus on functional noncoding RNAs and epigenetic regulation in ruminants. Results indicate that miRNAs play key roles in the regulation of milk fat synthesis and catabolism in ruminants. Although few data are available, merging evidence indicates that lncRNAs and circRNAs act on milk fat related genes through indirect action with microRNAs or RNAs in the ceRNA network to elicit positive effects on transcription. Although precise regulatory mechanisms remain unclear, most studies have focused on the regulation of the function of target genes through functional noncoding RNAs. Data to help identify factors that can regulate their own expression and function or to determine whether self-regulation involves positive and/or negative feedback are needed. Despite the growing body of research on the role of functional noncoding RNA in the control of ruminant milk fat, most data are still not translatable for field applications. Overall, the understanding of mechanisms whereby miRNA, lncRNA, circRNA, and ceRNA regulate ruminant milk fat remains an exciting area of research.